Draft Annual Plan 1980-81 Volume VII Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1980)
Jammu and Kashmir being a hilly State with Railway link only up to Jammu is entirely dependent for communication on the road network. A well-known road system is a pre-requisite not only for normal facilities of communication, but is the backbone for the development of the State in the fields of Agriculture, Animal Husbandry as well as for the exploitation of the Mineral, Industrial, Forest and Water resources. This makes the construction of additional roads and-up grading of the existing roads imperative, to assess the requirement of finances by the State for road development in the 6th Plan, a working group was set up by the State Planning Deptt. The need of the road sector was assessed, by the working group as Rs.300 crores in the State Sector. Against this, realizing the financial and other constraints. The working group recommended an allocation of Rs.1^0 crores for this sector. On further consideration the road Plan was reduced to Rs.103 crores. But tentative outlay for the road Sector in the 6th Plan period has subsequently 7 after discussion with planning commission.
Government of Jammu and Kashmir
Planning and Development Department Jammu
Keywords: State Motor Garages; Parks and Gardens; Land and Building; Acquisition of fleet; Establishment of District Depots; Disposal of sewerage of CD Hospital; Construction of Tourist Bungalow; Urban transport in Srinagar and Jammu Cities; Inter-State operation; Sight seeing operation in the Valley; State Government Contribution.